Active Fault-tolerant Control for Surface Permanent Magnet Synchronous Motor Under Demagnetization Fault - Ayyoub Zeghlache; Hemza Mekki; Ali Djerioui; Mohamed Fouad Benkhoris (My University, 2024)
This paper introduces a novel method for controlling a surface permanent magnet synchronous motor (SPMSM) during demagnetization fault conditions. The proposed fault-tolerant control (FTC) system incorporates a combination of a fuzzy extended state observer (FESO) based on an interval type 2 fuzzy logic controller (IT2FLC) and second-order sliding mode control (SOSMC) utilizing the super-twisting algorithm. The FESO aims to identify and eliminate demagnetization faults through reconstruction control. The FTC system enhances the dynamic performance and disturbance rejection of the SPMSM, providing a robust solution in the event of a demagnetization fault
Keywords: fault-tolerant control, surface permanent magnet synchronous motor, second-order sliding mode control, extended state observer, interval type 2 fuzzy logic controller